Insulin Resistance as a Major Risk Factor for Cardiovascular Disease - Canavan, Neil (MD Conference Express, 2008)
Insulin resistance is emerging as a major contributor to cardiovascular risk, and the lipotoxicity that is associated with obesity is a key factor in the development of insulin resistance. Recent data that suggest that thiazolidinediones may provide some insight into this issue are reviewed in this article.